Was the Green Revolution intended to maximise food production?. Issue 4 (4th July 2019) - Harwood, Jonathan
ABSTRACT: The evidence on yields, food-production, food-calories per capita, and declining levels of malnutrition in countries experiencing a Green Revolution are commonly cited in support of the claim that the GR sought to maximise food production. If one looks closely at the actual design of GR programmes (in India and elsewhere), however, it is clear that they were instead intended to boost yields and profitability in a small number of targeted areas. The underlying rationale for targeting was that achieving very high yields in such regions would persuade farmers to abandon subsistence farming in favour of commercial production, relying upon the market for the purchase of inputs as well as the sale of produce. In response to widespread criticism of the Green Revolution ca. 1970 for neglecting the needs of peasant farmers (as well as accentuating rural unrest), the World Bank and other donors began to direct more attention and resources to smallholders, but the aim of commercialising farming remained unchanged.